The Effect of Carbohydrates and Bacteriocins on the Growth Kinetics and Resistance of Listeria monocytogenes - Balay, Danielle R.; Gänzle, Michael G.; McMullen, Lynn M. (Frontiers in Microbiology, 2018)
The aim of this study was to determine if different carbohydrates influence the growth of Listeria monocytogenes in the presence of carnocyclin A or leucocin A. Carnobacterium maltaromaticum ATCC PTA-5313 and Leuconostoc gelidum UAL187 were used to produce carnocyclin A and leucocin A, respectively. Growth curves were modelled for 5 strains of L. monocytogenes grown in basal medium supplemented with glucose, sucrose, fructose, mannose, or cellobiose, in the presence of carnocyclin A or leucocin A. The growth of L. monocytogenes to leucocin A or carnocyclin A was influenced by carbohydrate and/or strain. Carnocyclin A inhibited the growth of L. monocytogenes more than leucocin A. Growth in media containing glucose, mannose, and fructose increased the sensitivity of some strains of L. monocytogenes to bacteriocins, while growth in cellobiose and sucrose increased the resistance of L. monocytogenes to bacteriocins, as evidenced by a shorter lag phase. Strains of L. monocytogenes developed resistance to both leucocin A and carnocyclin A, but the time to develop resistance was longer when strains are treated with carnocyclin A. Carbohydrate influences the development of resistance of L. monocytogenes to the bacteriocins, but the ability of strains to develop resistance to leucocin A or carnocyclin A differs. Results of this study indicate that carbohydrates influence the ability of L. monocytogenes to grow in the presence of bacteriocins.